2013
DOI: 10.3844/ajavsp.2013.89.97
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Overview of the Coxib Drugs in the Veterinary Field

Abstract: Traditional Non-steroidal Anti-Inflammatory Drugs (NAIDs) have been widely used to deal with many inflammatory conditions in veterinary medicine. Nowadays however, as the quality of life of animals is improved, new drug options need to be explored. In this review, the authors report on recent trends and the application of the active ingredients labeled for veterinary purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Currently the use of mavacoxib in the clinic is unorthodox as a result of the long half‐life of the drug potentially resulting in side‐effects which are problematic for the patient. The usual dosing regimen for mavacoxib comprises of administration at monthly intervals after initial doses of 2 mg/kg at day 0 and day 14, maintaining plasma concentrations at a steady state of around 0.52 to 1.11 μg/μL (1.35‐2.88 μM) . Studies have demonstrated that the safety profile of mavacoxib is comparable to other veterinary NSAIDs, and suggests that the benefits of reduced dosing should be exploited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently the use of mavacoxib in the clinic is unorthodox as a result of the long half‐life of the drug potentially resulting in side‐effects which are problematic for the patient. The usual dosing regimen for mavacoxib comprises of administration at monthly intervals after initial doses of 2 mg/kg at day 0 and day 14, maintaining plasma concentrations at a steady state of around 0.52 to 1.11 μg/μL (1.35‐2.88 μM) . Studies have demonstrated that the safety profile of mavacoxib is comparable to other veterinary NSAIDs, and suggests that the benefits of reduced dosing should be exploited.…”
Section: Discussionmentioning
confidence: 99%
“…The usual dosing regimen for mavacoxib comprises of administration at monthly intervals after initial doses of 2 mg/kg at day 0 and day 14, maintaining plasma concentrations at a steady state of around 0.52 to 1.11 μg/ μL (1.35-2.88 μM). 105,106 Studies have demonstrated that the safety profile of mavacoxib is comparable to other veterinary NSAIDs, 107,108 and suggests that the benefits of reduced dosing should be exploited. Although the concentrations of mavacoxib utilized in this study are higher than plasma concentrations, there is currently a concerted research effort to develop targeted drug delivery systems for cancer therapies which would allow increased concentrations of therapeutic agents to target the tumour site while minimizing undesirable side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…A therapeutic plan using effective and safe drugs is therefore needed. Nonsteroidal anti‐inflammatory drugs (NSAIDs) and selective cyclooxygenase (COX)‐2 inhibitors are mainstays of the pharmacopoeia for the treatment of signs and clinical signs of osteoarthritis and inflammatory pain of various aetiologies (Kim & Giorgi, ). However, these drugs still have an influence on the normal physiological condition of the patient and can produce adverse effects (KuKanich, Bidgood, & Knesl, ).…”
Section: Introductionmentioning
confidence: 99%
“…The COX-1 inhibition is shown to induce adverse gastrointestinal effects such as gastric erosion, ulceration and hemorrhage (Khan and McLean, 2012). The COX-2 inhibition has been recently found to correlate with kidney toxicity (Kim and Giorgi, 2013).…”
Section: Introductionmentioning
confidence: 99%